Structural and comparative analysis of R&D funding impact on the level of innovation development: The empirical evidence of GII’s leaders and Ukraine - Dobrovolska, Olena; Добровольська, Олена Володимирівна; Sonntag, Ralph; Зонтаг, Ральф; Ortmanns, Wolfgang; Ортманнс, Вольфганг; Kadyrus, Iryna; Кадирус, Ірина Григорівна; Rudyanova, Tatyana; Рудянова, Тетяна (LLC “Consulting Publishing Company “Business Perspectives”, 2023)
The study aims to determine the influence of the R&D expenditure structure funded by different sectors of stakeholders on the level of innovation development. The data sample involves values of GII and R&D expenditure funded by business, government, higher education, private non-profit sectors, and foreign sources for 10 countries – Ukraine and 9 top countries in GII-2022 for 2011–2020. Pearson/Spearman correlation analysis considers time lags to determine the nature and strength of relationships. For GII’s top countries, the relationship with innovation development level is confirmed as direct for funding R&D by business (in 8 from 9 countries), higher education (5 from 7), and foreign sources (5 from 9) with power from moderate to very high and 0-3-year lag. In Ukraine, the direct relationship is for financing by business (very high power and 3-year lag) and foreign sources (high power and 1-year lag). The regression modeling of dependences (Arellano-Bover/Blundell-Bond dynamic model for panel data and linear model for Ukraine) was also applied using STATA 18. In GII’s top countries, increasing the share of R&D expenditures financed by business by 1% contributes to increasing GII’s score by 0.25%, higher education – 2.47%; government, non-profit sector, and foreign sources – decreasing by 0.89%, 1.68% and 0.81% accordingly. In Ukraine, increasing financing R&D by the government by 1% leads to a similar decrease of GII estimate by 0.19% with a 2-year lag, and the business sector – an increase of 0.16% with a 3-year time lag. Vice versa, in Ukraine, R&D expenditures financed by higher education lead to GII’s score decreasing. Метою дослідження є визначення впливу структури витрат на НДДКР, що фінансуються різними секторами зацікавлених сторін, на рівень розвитку інновацій. Вибірка даних включає значення GII та видатків на дослідження та розробки, що фінансуються бізнесом, урядом, вищою освітою, приватним некомерційним сектором та іноземними джерелами для 10 країн – України та 9 країн з лідерами GII-2022 за 2011–2020 роки. Кореляційний аналіз Пірсона/Спірмена враховує часові лаги, щоб визначити характер і міцність зв’язків. Для кращих країн GII зв’язок із рівнем розвитку інновацій підтверджено як прямий для фінансування НДДКР бізнесом (у 8 із 9 країн), вищою освітою (5 із 7) та іноземними джерелами (5 із 9) із потужністю від середнього до дуже сильного. високий і 0-3-річний лаг. В Україні прямі відносини стосуються фінансування з боку бізнесу (дуже висока потужність і 3-річна затримка) та іноземних джерел (висока потужність і 1-річна затримка). Також було застосовано регресійне моделювання залежностей (динамічна модель Ареллано-Бовера/Бланделла-Бонда для панельних даних та лінійна модель для України) за допомогою STATA 18. У країнах-лідерах GII збільшення частки витрат на НДДКР, що фінансуються бізнесом, на 1% сприяє підвищення балу GII на 0,25%, вища освіта – 2,47%; уряд, некомерційний сектор та іноземні джерела – зменшилися на 0,89%, 1,68% та 0,81% відповідно. В Україні збільшення фінансування НДДКР державою на 1% призводить до аналогічного зниження оцінки GII на 0,19% з 2-річним лагом, а бізнес-сектором – зростання на 0,16% з 3-річним лагом. І навпаки, в Україні витрати на НДДКР, що фінансуються вищою освітою, призводять до зниження оцінки GII.
Структурно-порівняльний аналіз впливу фінансування НДДКР на рівень розвитку інновацій: емпіричні дані лідерів GII та України
Keywords: business; бізнес; development; розвиток; education; освіта; financing; фінансування; funding structure; структура фінансування; government; уряд; innovation; інновації; R&D; НДДКР